Tekstualisme Dan Kontekstualisme Penafsiran Kontemporer Terhadap Surah Al-Maidah Ayat 38 - Hidayati, Umi; Islamy, Athoillah (Institut Agama Islam Negeri Fattahul Muluk Papua, 2021)
Not only in the interpretation of classical scholars, the discourses on the interpretation of contemporary scholars are also diverse and often contradictory even though they are based on the same textual basis of the Qur'anic verse. This study intends to identify trends in the interpretation of contemporary scholars regarding the legal sanctions for cutting hands in al-Maidah verse 38. Two figures are studied, namely Ibn 'Asyur and Muhammad Syahrur. The main data objects of this research, namely the book (kitab) entitled al-Tahrîr wa al-Tanwîr by Muhammad Tahir Ibn 'Asyur and al-Kitâb wa al-Qur'ân Qirâ'ah Mu'âsirah by Muhammad Syahrur, and. The research approach used is a philosophical normative approach. The analytical theory used is the typology of textualism and contextualism of interpretation which was coined by Abdullah Saeed. Meanwhile, the nature of the research approach is descriptive-analytic. The results of the study conclude that the interpretation of Ibn 'Asyur regarding al-Ma'idah verse 38 can be categorized as a textual interpretation. This can be seen from his interpretation of the literal meaning of the verse. In addition, Ibn 'Asyur also tends to view the punishment of cutting off hands for thieves to be a deterrent as well as a preventive measure. In contrast to Ibn 'Asyur, Muhammad Syahrur's interpretation of the legal case of cutting off hands for thieves includes contextual interpretation. This can be seen when he understands the verse of cutting off hands for thieves, he gives a meaning that gives space for ijtihad for an area and conditions to enforce punishments that have a deterrent effect, provided that it must not exceed the punishment of cutting off handsas the maximum limit.